Resonant nano-electromechanical systems from 2D materials. (18th September 2020) - Hu, Kai-Ming; Bo, Peng; Li, Xiu-Yuan; Xin, Yi-Hang; Bai, Xin-Ru; Li, Lei; Zhang, Wen-Ming
Abstract: Intriguing mechanical properties of two-dimensional (2D) atomically thin materials make them well suit for a new class of resonant NEMS. Resonant 2D NEMS show high fundamental frequencies, outstanding tenability and broad dynamic range due to the ultrahigh strength, ultralow mass density and ultrahigh strain stretchability. Recent work toward exploring fabrication and transduction techniques, device performances and the nonlinear dynamic characteristics of 2D NEMS are summed up. Nonlinear dynamic behaviors including nonlinear mode coupling, nonlinear damping and nonlinear pull-in instability are reported in 2D NEMS.